From outwash to coastal systems in the Portneuf–Forestville deltaic complex (Québec North Shore): Anatomy of a forced regressive deglacial sequence. Issue 4 (8th February 2017) - Dietrich, Pierre; Ghienne, Jean‐François; Schuster, Mathieu; Lajeunesse, Patrick; Nutz, Alexis; Deschamps, Rémy; Roquin, Claude; Duringer, Philippe
Abstract: Deglacial sequences typically include backstepping grounding zone wedges and prevailing glaciomarine depositional facies. However, in coastal domains, deglacial sequences are dominated by depositional systems ranging from turbiditic to fluvial facies. Such deglacial sequences are strongly impacted by glacio‐isostatic rebound, the rate and amplitude of which commonly outpaces those of post‐glacial eustatic sea‐level rise. This results in a sustained relative sea‐level fall covering the entire depositional time interval. This paper examines a Late Quaternary, forced regressive, deglacial sequence located on the North Shore of the St. Lawrence Estuary (Portneuf Peninsula, Québec, Canada) and aims to decipher the main controls that governed its stratigraphic architecture. The forced regressive deglacial sequence forms a thick (>100 m) and extensive (>100 km 2 ) multiphased deltaic complex emplaced after the retreat of the Laurentide Ice Sheet margin from the study area ca 12 500 years ago. The sedimentary succession is composed of ice‐contact, glaciomarine, turbiditic, deltaic, fluvial and coastal depositional units. A four‐stage development is recognized: (i) an early ice‐contact stage (esker, glaciomarine mud and outwash fan); (ii) an in‐valley progradational stage (fjord head or moraine‐dammed lacustrine deltas) fed by glacigenics; (iii) an open‐coast deltaic progradation, when proglacial depositional systems expanded beyond the valley outlets and merged together; and (iv) a final stage of river entrenchment and shallow marine reworking that affected the previously emplaced deltaic complex. Most of the sedimentary volume (10 to 15 km 3 ) was emplaced during the three‐first stages over a ca 2 kyr interval. In spite of sustained high rates of relative sea‐level fall (50 to 30 mm·year −1 ), delta plain accretion occurred up to the end of the proglacial open‐coast progradational stage. River entrenchment only occurred later, after a significant decrease in the relative sea‐level fall rates (<30 mm·year −1 ), and was concurrent with the formation and preservation of extensive coastal deposits (raised beaches, spit platform and barrier sands). The turnaround from delta plain accretion to river entrenchment and coastal erosion is interpreted to be a consequence of the retreat of the ice margin from the river drainage basins that led to the drastic drop of sediment supply and the abrupt decrease in progradation rates. The main internal stratigraphic discontinuity within the forced regressive deglacial sequence does not reflect changes in relative sea‐level variations.